Effect of heat stress on the expression patterns of different reproduction related genes in Malabari goats - Amitha, J Pai (Academy of Climate Change Education and Research, 2018)
Heat stress is the major factor which negatively influences the reproductive performance of ruminant livestock. Although there are several reports which established the adverse impacts of heat stress on the reproductive performance of goats, studies pertaining to heat stress influence on hypothalamic-pituitary-gonadal (HPG) axis associated genetic traits are very meagre. Therefore, the study was conducted with the primary objective of establishing the effect of heat stress on expression patters of different traits that controls Malabari goat reproduction. The study was conducted during 45 days using twelve 10 months to one year old Malabari goats. The goats were randomly allocated into two groups: MC (n=6; Malabari control) and MHS (n=6; Malabari heat stress). Goats were stall - fed with a diet composed of 60% roughage and 40% concentrate. All animals had access to ad-libitum feed and water and they were fed and watered individually. The MC goats were placed in the shaded pens while MHS goats were exposed to heat stress in outside environment between 10.00 h to 16.00 h. At the end of study period, all 12 animals were slaughtered and their uterus tissues were collected for gene expression and histopathological studies. The temperature humidity index (THI) inside shed (74.9) proved that the animals were not stressed while in the outside environment (86.5) the animal were extremely distressed. Heat stress significantly (P<0.05) influenced the expression patterns of estrogen receptor α (ESTRα), prostaglandin F2 α (PGF2α) and prostaglandin E2 (PGE2). Further, a strong positive correlation (P<0.01) was established for THI with both PGF2α and PGE2 gene expressions. However, heat stress did not influence the expression patterns of follicle stimulating hormone receptor (FSHR), luteinizing hormone receptor (LHR) and cyclooxyxgenase-2 (COX-2) genes. Further, the non-significant correlation of THI with FSHR, LHR and COX-2 could be attributed to the resilience capacity Malabari breed to heat stress. The histopathological section of uterine epithelial cells showed degenerative changes (P<0.05) with less differentiation in MHS group as compared to MC group. Therefore, the results obtained from the study on the establishment of heat stress associated changes on the expression patterns of the various HPG axis genes is the first of its king in domestic animals. The results from the study clearly indicated that heat stress was able to alter reproductive activity related gene expression at uterine level to reduce the reproductive efficiency in Malabari goats. The study also indicated that ESTRα, PGF2α and PGE2 genes could serve as ideal indicators of heat stress effect on reproductive performance in indigenous Malabari goats. Keywords: Climate change; ESTRAα; Heat stress; PGF2α; PGE2 Reproductive trait.